Linguistic Diversity In English Classrooms: A Systematic Review And Theoretical Framework For Inclusive ELT Practices - Sholikhah, Yayang Imroatus; Al-Farizi, M Furqon; Sari, Ayunia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This systematic review study highlights the importance of critical multicultural education in promoting social justice, dialogic pedagogy and critical consciousness in line with Original Critical Pedagogy by Paulo Freire and Critical Pedagogy Revised by Antonia Darder, emphasizing evolution towards social justice. This study proposes the inclusion of critical multicultural education in teacher education programs and its wider implementation in culturally diverse environments. By combining diverse perspectives and experiences, this approach aims to foster critical thinking and empower students to navigate and appreciate the complexity of diverse cultural landscapes. This research uses a systematic review approach. The search strategy yielded thousands of studies for inclusion in the systematic keyword map, and 23 studies for in-depth review. The findings of this systematic review reveal that critical multicultural education is essential for empowering students. This study advocates its application in diverse contexts, emphasizing the release of cultural norms and promoting an equitable environment. Teacher education can promote diverse content, challenge power dynamics, and encourage critical thinking, thereby contributing to an egalitarian society. In conclusion, critical multicultural education is essential for an inclusive society, empowering all students and fostering a just society.